Mobile phones, sexual socialization and media literacy: perceptions and challenges in digital protection of children and adolescents - Establés, María-José (2025)
Sexual objectification is one of the ways young people socialize on social media and has become a challenge in digital child and adolescent protection due to its impact on sexual maturity and self-esteem. This research aims to understand the perceptions of both experts and young people regarding sexual socialization, as well as the motivations behind adolescents' use of sexual content they consume and/or exchange on social media. The methodology consisted of 14 semi-structured interviews with experts and a survey conducted with 421 adolescents who participated in digital sexual education workshops between 2022 and 2024. The results show that experts identify approval—through sexual display—as a key factor in adolescents' use of social media. However, most young people do not perceive a risk in using social media to send nude images of their bodies, either for themselves or others, as they consider it a private matter. The research encourages reflection on the fact that young people value their bodies as the most important aspect of their personality, highlighting the need for improvements in media education. It also provides arguments for policymakers, the technology sector, educators, and families regarding digital child protection.